2021
DOI: 10.1089/vbz.2021.0049
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sylvatic Plague Vaccine Does Not Adequately Protect Prairie Dogs (Cynomys spp.) for Endangered Black-Footed Ferret (Mustela nigripes) Conservation

Abstract: The plague bacterium Yersinia pestis is lethal to endangered black-footed ferrets ( Mustela nigripes , BFF) and the prairie dogs ( Cynomys spp., PD) on which they depend for habitat and prey. We assessed the effectiveness of an oral sylvatic plague vaccine delivered in baits to black-tailed PD ( Cynomys ludovicianus , BTPD) from 2013 to 2017 on the Charles M. Russell National Wildlife Refuge (CMR) in northcentral Montan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…As stated earlier in the Methods section, we acknowledge that population fluctuations in BTPDs did not necessarily equate to disease dynamics, as we did not have concomitant disease data during each colony die-off. Although we were confident that large-scale extinctions were due to plague in our study, this confidence may be restricted to our study area (i.e., central Great Plains), where much work has confirmed the pattern of spread and effects of plague on BTPD colonies (e.g., Cully et al, 2010;Johnson et al, 2011;Matchett et al, 2021). Thus, researchers should exercise caution when applying our model to grasslands outside of our study area, such as more southern grasslands where drought can result in colony contractions (e.g., Ceballos et al, 2010;Facka et al, 2010).…”
Section: Caveatsmentioning
confidence: 79%
See 1 more Smart Citation
“…As stated earlier in the Methods section, we acknowledge that population fluctuations in BTPDs did not necessarily equate to disease dynamics, as we did not have concomitant disease data during each colony die-off. Although we were confident that large-scale extinctions were due to plague in our study, this confidence may be restricted to our study area (i.e., central Great Plains), where much work has confirmed the pattern of spread and effects of plague on BTPD colonies (e.g., Cully et al, 2010;Johnson et al, 2011;Matchett et al, 2021). Thus, researchers should exercise caution when applying our model to grasslands outside of our study area, such as more southern grasslands where drought can result in colony contractions (e.g., Ceballos et al, 2010;Facka et al, 2010).…”
Section: Caveatsmentioning
confidence: 79%
“…Thus, within colonies that suffered greater than 50% loss in area between years, we classified raster cells that transitioned from occupied by BTPDs to unoccupied as extinction events due to plague. We were confident that these large‐scale extinction events were primarily attributable to plague because plague is the only disease known to cause extensive die‐offs among BTPDs over short time periods (Barnes, 1993), and no other mechanism (e.g., predation, drought) is likely to cause the extreme population reductions that could be confused with the effects of plague (e.g., Colman et al, 2021; Cully et al, 2010; Johnson et al, 2011; Matchett et al, 2021). Indeed, serological testing of BTPD carcasses and fleas collected in and around burrows confirmed the presence of the plague bacterium at all eight of our study sites (Cully et al, 2010; Johnson et al, 2011; Savage et al, 2011; Thiagarajan et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…We recommend fipronil bait treatments in mid-to late summer for BTPDs because Abbott et al (2018) and Matchett et al (2021) showed high levels of bait uptake under those conditions, while Eads et al ( , 2020Eads et al ( , 2021 showed effective flea control on BTPDs with fipronil bait treatments during the same time periods. We recommend similar treatment timing for GPDs, Utah PDs (Cynomys parvidens) and white-tailed PDs (Cynomys leucurus), considering that treatments need to be completed before the onset of hibernation.…”
Section: Discussionmentioning
confidence: 99%
“…Trap effort and sampling procedures were identical and simultaneous on paired treated and nontreated plots. Detailed PD handling methods can be found in Eads et al ( , 2020Eads et al ( , 2021 and Matchett et al (2021). Briefly, we live-trapped PDs using cage traps (Tomahawk Live Trap, Hazelhurst, Wisconsin, USA in South Dakota and Arizona; Tru-Catch Traps, Belle Fourche, South Dakota in Montana) baited with a rolled corn, oats, barley, and molasses livestock feed (laced with small amounts of peanut butter in South Dakota).…”
Section: Fipbits Used Inmentioning
confidence: 99%
See 1 more Smart Citation